Brugada syndrome genetic testing: A reliable sanger sequencing protocol. (December 2015) - Cisana, S.; Verzeletti, A.; Vassanelli, F.; Bontempi, L.; Cerri, N.; Cortellini, V.; Curnis, A.; De Ferrari, F.
Abstract: The Brugada syndrome (BrS) is a potentially lethal, inheritable arrhythmia syndrome affecting about 5 in 10, 000 people worldwide. This cardiac disorder, triggered by mutations in SCN5A gene (encoding for cardiac sodium channels), results in changes in the onset or propagation of cardiac action potential that can generate arrhythmias, potentially fatal. In the last few years, the genetic studies are performed with next generation sequencing (NGS), obtaining global genomic information. However, this strategy requires capillary electrophoresis data validations. In this study, we developed and optimized a Sanger sequencing workflow for SCN5A gene exons.